Morphology and molecular phylogeny of two new Aspidisca species (Ciliophora, Spirotrichea, Euplotida) collected from subtropical coastal waters in China - Zheng, Bohan; Zhao, Xuetong; Ye, Tingting; Huang, Jie; Vallesi, Adriana; Jiang, Yaohan; Chen, Xiangrui (Frontiers in Marine Science, 2022)
Ciliates are morphologically diverse and highly specialized unicellular eukaryotes that constitute an important component of the microbial food web. Aspidisca Ehrenberg, 1830 is a highly speciose genus that plays key ecological roles in a wide range of environments, and its species diversity has always been a hot spot in protozoan research. In this study, we investigate the living morphology, infraciliature, silverline system and ribosomal small subunit (SSU rRNA) gene sequences of two new Aspidisca species collected from subtropical coastal waters of China using standard methods. Aspidisca spina sp. n. is characterized by having an obvious peristomial spur, two transparent posterior protrusions, seven frontoventral cirri in “polystyla-arrangement” and six dorsal ridges. It can be distinguished from the most similar congener, A. magna Kahl, 1932, by the presence of posterior protrusions, more membranelles in the posterior part of adoral zone (AZM2), and different SSU rRNA gene sequences. A. shini sp. n. is smaller in body size, only 35–40 × 25–30 µm in vivo, with four prominent ridges on the arched dorsal side, very similar with the “well-known” species A. steini Buddenbrock, 1920 in morphological characteristics, but it can be distinguished by the arrangement of frontoventral cirri and 121 nucleotides difference in the SSU rRNA gene sequences. Phylogenetic analyses based on the SSU rRNA gene sequences revealed the systematic positions of two new taxa and supported the validity of them as distinct species.